Mangrove outwelling is a significant source of oceanic exchangeable organic carbon. Issue 1 (29th January 2017) - Sippo, James Z.; Maher, Damien T.; Tait, Douglas R.; Ruiz‐Halpern, Sergio; Sanders, Christian J.; Santos, Isaac R.
Abstract: Exchangeable dissolved organic carbon (EDOC) makes up a significant proportion of the oceanic dissolved organic carbon (DOC) pool, yet EDOC sources to the coastal ocean are poorly constrained. We measured the exchange of EDOC and concentrations of EDOC and DOC in mangrove waters over a 26° latitudinal gradient. A clear latitudinal trend was observed, with the highest EDOC concentrations in the tropics. EDOC exports to the coastal ocean were 4.7 ± 1.9 mmol m −2 d −1, equivalent to 11% of DOC exports (42.1 ± 6.7 mmol m −2 d −1 ). Pore‐water and groundwater exchange were minor sources of EDOC. EDOC concentrations were equal to 13% ± 4% of DOC concentrations. Based on previous global DOC export estimates, and our EDOC : DOC ratios, mangroves outwell 3.1 Tg C yr −1 as EDOC, equivalent to ∼ 60% of the global EDOC flux from the ocean to the atmosphere. However, seasonality of mangrove EDOC cycling requires further research.